Deep Lab v3+: A Novel Deep Learning Model for Accurate and Efficient GTV Segmentation and Classification in NSCLC Imaging - Atiya, Shaik Ummay; Ramesh, N. V. K. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
This research proposes an innovative methodology for accurate Gross Target Volume (GTV) segmentation and classification in Non-Small Cell Lung Cancer (NSCLC) treatment planning. The proposed method is based on the DeepLab v3+ model and employs a comprehensive strategy to address the challenges of class imbalance, including weighted loss, data augmentation, selective sampling, and post-processing techniques. In this paper, the Kaggle chest CT scan dataset is employed, and the proposed model is trained over 50 epochs. The model achieves remarkable results across various evaluation metrics, including a Dice coefficient of 0.87, Jaccard similarity coefficient of 0.84, true positive rate of 0.94, and false positive rate of 0.0011. The model also achieves an impressive segmentation time of 25 ms per slice. In the classification realm, the model achieves accuracy scores of 96.7% for tumor, 95.3% for lymph node, and 94.2% for healthy tissue classifications. The proposed method outperforms existing methods, such as U-Net and Modified ResNet models, in key metrics. This is due to its complex architecture, multi-scale approach, and employment of dilated convolutions. These distinctive attributes empower the model to excel in accurate and efficient GTV segmentation and classification, enhancing the clinical workflow for NSCLC treatment planning. The implications of this research are vast, as the proposed method’s precision and efficiency can revolutionize the accuracy of GTV delineation, paving the way for more informed and effective treatment decisions in NSCLC patients.